Gemcitabine-associated thrombotic microangiopathy - a role for eculizumab? - Chuva,Teresa (2019)
Gemcitabine-associated thrombotic microangiopathy (gTMA) is a rare entity that is usually associated with a poor prognosis, with loss of kidney function and often death. The management of this syndrome includes discontinuation of the drug. Other approaches have been tried, with no proven efficacy and inconsistent results, such as glucocorticoids, intravenous immunoglobulin, plasma infusion and rituximab. Drug-induced hemolytic uremic syndrome, a form of thrombotic microangiopathy (TMA), has shown good response to the anti-C5 monoclonal antibody eculizumab and anecdotal cases have been reported where eculizumab improved gTMA. We present a case where a patient with gTMA on hemodialysis was treated with eculizumab, with full recovery of hematological disorders and kidney function. We suggest that clinicians be aware of gTMA as a potentially life-threatening condition and that eculizumab should be considered as a possible first-line agent.